Labor Demand and Trade Reform in Latin America - Fajnzylber, Pablo; Maloney, William F. (World Bank, Washington, DC, 2014)
There are concerns that trade reform and globalization will increase the uncertainty that the average worker, especially the relatively unskilled worker, faces. The increased competitiveness of product markets and greater access to foreign inputs, the argument goes, will lead to more elastic demand for workers. This may have adverse consequences for both labor market volatility and wage dispersion. The authors argue that while the case that trade liberalization should increase own-wage elasticities may be broadly compelling for competitive import-competing industries, it is less so for imperfectly competitive, nontradable, or export industries. They test the hypothesis using establishment-level panel data from three countries with periods of liberalization. The data provide only mixed support for the idea that trade liberalization has an impact on own-wage elasticities. No consistent patterns emerge. If globalization is making the lives of workers more insecure, it is probably working through some other mechanism.